Educação, imagem e comunicação multimídia: comunicação e conhecimento tácito - Canastro, Dirce Sales de Mesquita (2010)
This work aims to analyze Education and Communication s importance, along with information technology, as constituents of reflexive changes of how human beings build their knowledge and transmit their experiences and values. In attempt to better understand how works this process, we look forward to contextualize how occur these interactions, through analysis of some communicational models used on education and of media s interference on school context. To use communication (learn by doing) is the best methodology to make students exert their expression rights for a democratic Education. Comprehending this reality Mário Kaplun used the term Educommunication applied for communitarian questions awareness, the mediaeducation, in other words to build new communicative ecosystems, which demand prepared and qualified persons to use these techniques at NGOs, churches, museums and schools. The research leads to a deliberation about how Communication is the element whereby human being changes himself in to subject of his own history, in the picture of a transdisciplinarity that (Prigogine,1996) mentions and declares the end of certainties and knocks down any theory intended to be definitive. Thus transdisciplinarity introduces a new age in education for Communication (Freire) based on ethical order principles, on democratic values and of tacit knowledge (Pollanyi, 1959). This work is the beginning of a debate that valorizes education/communication interface s discovery which in the picture of new technologies comes to emphasize it s implications for teacher s formation and praxis